Transformasi Teknologi dan Tantangan Regulatori dalam Pengembangan Pasar Modal Syariah di Indonesia - Junaidi Junaidi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Indonesia's Sharia capital market has experienced significant growth in the past decade, along with rising public awareness of Islamic economic principles and the adoption of digital technologies. This study aims to analyze the role of digital transformation in supporting the development of the Sharia capital market and to identify structural challenges, particularly in regulatory, financial literacy, and cybersecurity aspects. The methodology used is descriptive qualitative with a literature study approach, drawing on secondary data from reputable journals and official publications from OJK and the Indonesia Stock Exchange. The results indicate that while technological transformation has opened significant opportunities such as increased financial inclusion and youth investor engagement, the Sharia capital market still faces serious challenges related to unadaptive regulations, cyber threats and low investor literacy. This study recommends synergy between regulators, industry players and educational institutions to strengthen a sustainable Sharia capital market ecosystem.